Home bias in bank sovereign bond purchases and the bank-sovereign nexus - Desislava C. Andreeva; Thomas Vlassopoulos (European Central Bank (ECB), 2016)
We study whether a pre-existing link between bank and sovereign credit risk biased euro area banks' sovereign debt portfolio choices during 2011Q4 and 2012Q1 – a period of exceptional increases in their domestic sovereign bond holdings. We find that banks whose creditworthiness is linked to that of the respective sovereign tended to purchase higher amounts of domestic sovereign bonds relative to their main assets if the CDS spreads on domestic sovereign bonds were higher. Moreover, for elevated sovereign CDS levels, banks whose creditworthiness is ex ante more strongly positively correlated with that of the local sovereign exhibit larger purchases of domestic government bonds. These findings are consistent with 'risk shifting' behaviour, where by investing in domestic government bonds banks earn the full, high risk premium while the risk is largely borne by their creditors as it materialises in states of the world where the banks are likely to be insolvent anyway. As a result, domestic sovereign debt offers ex ante higher returns to bank shareholders than alternative ways to build up precautionary liquidity buffers or indeed to execute carry trades, such as to invest in non-domestic government bonds.
Keywords: G01; G11; G21; H6; 330; bank-sovereign nexus; sovereign default